An ɑ2-adrenergic receptor is involved in larval metamorphosis in the mussel, Mytilus coruscus. Issue 9 (21st October 2019) - Liang, Xiao; Chen, Ke; Li, Yi-Feng; Bao, Wei-Yang; Yoshida, Asami; Osatomi, Kiyoshi; Yang, Jin-Long
Abstract: Metamorphosis is crucial in the life-cycle transition between the larval and juvenile stages of marine invertebrates. Although a number of agonists and antagonists of the adrenergic receptor (AR) are known to regulate larval metamorphosis in Mytilus coruscus (Mc), the molecular basis of the modulation of larval metamorphosis by the AR gene in this species remains elusive. Herein, the role of the AR gene in M. coruscus larval metamorphosis using the RNA interference technique was examined. The Mcα2 AR transcript was observed to be present during the entire process of larval development and its level in the post-larvae was significantly increased compared to that in the pediveligers. Mcα2 AR-knockdown resulted in a substantial reduction in the abundance of the Mcα2 AR transcript and significantly inhibited the metamorphosis of M. coruscus larvae. These findings provide new insights into the molecular basis of modulation of larval metamorphosis in M. coruscus by the AR gene.